Recontextualization of Hadith in TikTok Youth Culture - Achmad Syukron; Zulfirman Manik; Nur Asikin Siregar; Desi Herawati Bintang; Alif Sutansyah Lubis (Yayasan Bayt Shufiya Nusantara, 2025)
This study investigates how hadith is recontextualized within TikTok’s viral culture, where short videos, humor, memes, and colloquial expressions increasingly shape the modes of Islamic da'wah. The rapid circulation of religious content on TikTok raises concerns regarding simplification, potential distortion, and the authority of hadith-based messages. Addressing this problem, the study aims to analyze the strategies used by digital creators to present and adapt hadith within a highly visual and fast-paced environment. Utilizing qualitative content analysis of trending hadith-centered da'wah videos and drawing on media recontextualization and digital religion frameworks, the findings show that creators commonly emphasize moral, motivational, and emotional elements to enhance accessibility for younger audiences. However, the study also identifies challenges such as meaning reduction, the spread of non-credible sources, and the commodification of religion driven by engagement metrics. The study concludes that while TikTok expands the reach of hadith-based da'wah, ensuring accuracy and ethical communication requires digital religious literacy, source verification, and collaboration among scholars and content creators.